Generalized stacking faults energies of face-centered cubic high-entropy alloys: A first-principles study. (June 2022) - Li, Xiaojie; Schönecker, Stephan; Vitos, Levente; Li, Xiaoqing
Abstract: Developing high-strength and ductile face-centered cubic (fcc) high-entropy alloys (HEAs) has attracted significant attention. The generalized stacking fault energy (GSFE) is a very useful concept to describe stable and unstable planar defects and their energies on a slip plane. It plays an essential role in designing high performance fcc HEAs and understanding the nanoscale plasticity phenomena. In this work, using first-principles simulations, we investigate the configuration-averaged GSFEs of 29 single-phase fcc HEAs and identify indicators that can be used to tune stacking fault energies. First we determine the equilibrium structural parameters for all considered alloys and compare them with available experimental data. With the obtained GSFEs, we analyze the relationship between the stacking fault energies and materials properties, and investigate scaling relations between planar fault energies and the tendencies to exhibit deformation twinning and transformation to hexagonal close-packed martensite. We find that unstable SFE and shear modulus correlates strongly. Moreover, we reveal that the ratio of intrinsic SFE to unstable SFE, γ isf / γ usf, is a characteristic materials measure, and the tendencies to twinning and martensitic transformation rank with it. Our results are expected to be useful for an efficient alloy design and selection of solutes in fcc HEAs. Graphical abstract: Image 1 Highlights: Unstable stacking fault energy (SFE) and shear modulus correlate strongly. Four planar defect energies satisfy two scaling relations; one relation proposed here. Ratio of intrinsic SFE to unstable SFE (Λ) is a characteristic materials measure. Tendencies to twinning and martensitic transformation rank with Λ.